HISTORY OF AGRICULTURAL TECHNOLOGIES IN THE PROCESSING OF COTTON PRODUCTS AT THE SURKHANDARYA OASIS - Dilaram Tadjiyevna, Yakubova (PT. Antis International Publisher, 2025)
Objective: This study investigates the historical development of fine-fiber cotton production in the Surkhandarya oasis, Uzbekistan, focusing on agro-technological advancements and irrigation reforms during the Soviet era. It aims to highlight the scientific contributions and climatic adaptations that facilitated cotton cultivation in this region. Method: The research employs a historical analysis based on archival sources, government reports, and scientific studies to examine the role of agricultural policies, experimental farms, and irrigation projects in fine-fiber cotton production. Results: The findings reveal that Surkhandarya’s unique climatic conditions, particularly temperature stability and low humidity, were crucial for fine-fiber cotton cultivation. Soviet agricultural initiatives, including soil studies and irrigation networks, significantly enhanced production efficiency. Moreover, scientific research played a pivotal role in developing resilient cotton varieties suited to the region’s agro-climatic characteristics. Novelty: Unlike previous studies that broadly discuss Soviet cotton policies, this research provides a focused examination of the specific agro-technological advancements and environmental adaptations that shaped fine-fiber cotton cultivation in Surkhandarya. Understanding these historical agricultural strategies offers valuable insights for improving contemporary cotton production and sustainable farming practices in arid regions.